ЭКОЛОГИЯЛЫҚ КРИЗИСТИҢ КЕСКИНЛЕСИЎИНИҢ ҲӘЗИРГИ БАСҚЫШЫНДА «ТӘБИЯТ-ЖӘМИЙЕТ» СИСТЕМАСЫН ИЗЕРТЛЕЎДИҢ ТИЙКАРҒЫ МЕТОДОЛОГИЯЛЫҚ УСЫЛЛАРЫ - Бердимуратова, А.К. (FAN va JAMIYAT, 2021)
This article discusses the exacerbation of the modern ecological situation in its correlation with the systemic connection with society and nature. Disclosed the content of the activity-transforming, historical-materialistic, socio-ecological methodological methods in relation to socio-natural development within the framework of the system approach.